Longitudinal assessment of interstitial lung disease in single lung transplant recipients with scleroderma. (27th August 2019) - Hinze, Alicia M; Lin, Cheng T; Hussien, Amira F; Perin, Jamie; Venado, Aida; Golden, Jeffrey A; Boin, Francesco; Brown, Robert H; Wise, Robert A; Wigley, Fredrick M
Abstract: Objective: To investigate the natural history of fibrotic lung disease in recipients of a single lung transplant for scleroderma-associated interstitial lung disease (ILD). Methods: Global ILD (including ground glass, nodular opacities and fibrosis) was categorized into severity quintiles on first and last post-transplant CT scans, and percent fibrosis by manual contouring was also determined, in nine single lung transplant recipients. Quantitative mean lung densities and volumes for the native and allograft lungs were also acquired. Results: In the native lung, global ILD severity quintile worsened in two cases and percent fibrosis worsened in four cases (range 5–28%). In the lung allograft, one case each developed mild, moderate and severe ILD; of these, new fibrotic ILD (involving <10% of lung) occurred in two cases and acute cellular rejection occurred in one. The average change in native lung density over time was +2.2 Hounsfield Units per year and lung volume +1.4 ml per year, whereas the allograft lung density changed by –5.5 Hounsfield Units per year and total volume +27 ml per year ( P = 0.011 and P = 0.039 for native vs allograft density and volume comparisons, respectively). Conclusions: While the course of ILD in the native and transplanted lungs varied in this series, these cases illustrate that disease progression is common in the native lung, suggesting that either the immune process continues to target autoantigens or ongoing fibrotic pathways are active in the native lung. Mild lung disease may occur in the allograft after several years due to either allograft rejection or recurrent mild ILD.